THE METHODS USED IN THE EXPLANATION OF GENETIC CONSISTENCY IN CHEMISTRY AND THE ROLE OF THE CHEMICAL EXPERIMENT - D.B. Jabborova (American Journals, 2023)
The article talks about the use of effective methods and the role of chemical experiments in explaining the genetic consistency of inorganic and organic compounds.
Keywords: Organic, experiment, venn diagram, cluster, snake, chemical puzzles, heuristic conversation.